Credit risk management basic concepts : financial risk components, rating analysis, models, economic and regulatory capital - Gestel, Tony van.; Baesens, Bart. (Oxford : Oxford University Press, 2009)
This text lays the foundations of credit risk management defining the basic risk concepts and providing an overview of a risk modelling process. It provides an introduction to financial risk management, discussed in terms of practical business impact, and the increasing profitability competition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Credit; Financial risk management